The influence of lawbreaking animal rights activists on their family members: the familial-ideological spin model - Inbar-Frohlich, Tali (Journal of crime and justice, 2022)
Ideological delinquency of animal rights activists has been studied, but there is a lack of research into its impact on family members. The present study examines how 18 family members (nine parents, nine partners) of ideological lawbreaking animal rights activists perceived their relationship with the activists. The analysis of semi-structured interviews describes the reasons the family members joined activism and the differences between those who became law-abiding vs. those who became lawbreaking activists. The familial-ideological spin model explains the process of ‘infection’ by which family members can be drawn into ideological activity; some of them may experience familial-ideological criminal spin.